Efektifitas Konseling Kelompok Teknik Modelling untuk Meningkatkan Ketahanan Akademik Siswa - Mustakim, Ichwanul (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2025)
The purpose of this study is to find out the effectiveness of group counseling with modeling techniques to improve students' academic resilience, this study was conducted on students to see the extent to which their academic resilience has increased, the data collection method in this study was using one group pre-test post-test, the population was 30 students who were given a pre-test and the sample used purposive random sampling with 8 students who would be given treatment in the form of group counseling with modeling techniques to improve their academic resilience, while data collection used a questionnaire as the main method. Data analysis used a non-parametric statistical test, the t-test. the results obtained in this study were t-count of 7,399 while the t-table was 2,365 in other words that the t-count was greater than the t-table (7,399 ˃ 2,365). so that the null hypothesis (Ho) proposed was not accepted and the alternative hypothesis (Ha) was accepted. It can be interpreted that group counseling with modeling techniques is effective in improving students' academic resilience.